Health Complaints Associated with Poor Rental Housing Conditions in Arkansas: The Only State without a Landlord’s Implied Warranty of Habitability - Bachelder, Ashley E.; Stewart, M. Kate; Felix, Holly C.; Sealy, Neil (Frontiers in Public Health, 2016)
Arkansas is the only U.S. state that does not have a landlord’s implied warranty of habitability, meaning tenants have a requirement for maintaining their rental properties at certain habitability standards, but landlords are not legally required to contribute to those minimum health and safety standards. This project assessed the possibility that this lack of landlord responsibility affects tenants’ perceived health. Using surveys and interviews, we collected self-reported data on the prevalence and description of problems faced by renters who needed household repairs from their landlords. Of almost 1,000 renters, one-third of them had experienced a problem with their landlord making needed repairs; and one-quarter of those had a health issue they attributed to their housing conditions. Common issues included problems with plumbing, heating, or cooling systems, and pest or rodent control. Reported health problems included elevated stress levels, breathing problems, headaches, high blood pressure, and bites or infections. Hispanic respondents and those with less than a high school education were both significantly more likely to report problems with their landlords not making repairs as requested. These data suggest that the lack of landlord requirements may negatively impact the condition of rental properties and, therefore, may negatively impact the health of Arkansas renters.